Programa de qualidade de vida no trabalho na Universidade Federal de Alfenas - UNIFAL-MG - campus sede: um estudo de caso - Sanches, Marco Aurélio (2018)
The present study was carried out with the main objective of analyzing the Work Quality of Life Program ((QWL) programs) of UNIFAL-MG – headquarters campus, within the framework of its servers. Through the research, it was possible to understand that QWL involves a set of actions that stimulate a healthy work environment, contributing to the development of QWL indicators that become an instrument that provides strategies, actions and debates, contributing to the prevention of diseases and in the elaboration of personnel management policies, thus reducing absenteeism rates. In this investigation, a case study was sought: 1) Evaluate the perception and satisfaction of the faculty and administrative staff in education of UNIFAL-MG that participate in the (QWL) programs in the FIEH; 2) Evaluate the perception of management over of servers in the (QWL) programs; 3) Check the reason for the non-participation of servers in the (QWL) programs; 4) To analyze the overall total of server absences due to medical problems (data inserted in an internal software of the Integrated Subsystem of Attention to the Health of the Server (System SIAPE Health / SIASS); 5) Identify the causes of absenteeism, and; 6) Identify and propose opportunities for improvement in the (QWL) programs, within UNIFAL-MG.